HUBUNGAN ERGONOMI KERJA DENGAN KELUHAN MUSKULOSKELETAL PADA PEGAWAI PT. BANK NEGARA INDONESIA (PERSERO).TBK KANTOR CABANG SINGKAWANG - Zulkarnain Edward; Luis Yulia; Nopri Esmiralda; ivanna, Ivanna Dwi Putri Riyanto (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Suboptimal ergonomic can trigger various health issues, including musculoskeletal disorder. Musculosceletal Disorder, characterized by pain in muscles, joints, tendons, and the skeletal system, can affect individuals in diverse work sectors, including office environments. Bank employees, such as those at PT. Bank Negara Indonesia Singkawang Branch Office, are particularly susceptible to these pains due to poor work ergonomic. Prolonged sitting or standing with improper postures can lead to various problems such as pain, aches, and stiffness in various body parts. Methods: This study uses a quantitative analytical design with a cross-sectional approach conducted at PT. Bank Negara Indonesia Singkawang Branch. The sample used in this study was all employees working at the Singkawang City Branch and Diponegoro Sub-Branch offices. The research results were tested using the chi-square test. Results: The results of this study showed p-value of 0.012 (p <0.05) was obtained, indicating that there is a relationship between work ergonomics and musculoskeletal complaints. Conclusion: Based on the research results, it was found that there is a relationship between Work Ergonomics and Musculoskeletal Complaints in employees of PT. Bank Negara Indonesia Keywords: Work Ergonomic, Musculosceletal disorder, Pain